(untitled) (Journal of Asian Development Studies, 2016)
Capacity Building is the very important phenomenon in the development of any nation or state. The states give due value towards capacity building process. The main theme of the research is to highlight the significance of the capacity building. It also focuses on he process, methods and techniques in this regard. The research highlights the pitfalls during this process faced by developing countries. The approach is analytical and descriptive. The original and secondary sources are used. Suggessions and conclusion are in the end.